1997
DOI: 10.1021/ma970491g
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Degradation and Adsorption on Poly[(R)-3-hydroxybutyrate] Single Crystals with Two Types of Extracellular PHB Depolymerases from Comamonas acidovorans YM1609 and Alcaligenes faecalis T1

Abstract: Poly[(R)-3-hydroxybutyrate] (P(3HB)) single crystals, which had different morphologies with and without chain-folding surfaces, were grown from dilute solutions of chloroform and ethanol. Two types of extracellular PHB depolymerases purified from Alcaligenes faecalis T1 and Comamonas acidovorans YM1609, defined as types I and II according to the position of the lipase box in the catalytic domain, were used in the enzymatic degradation and adsorption experiments. The enzymatic degradation of P(3HB) single cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
135
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 99 publications
(148 citation statements)
references
References 40 publications
(90 reference statements)
12
135
1
Order By: Relevance
“…Furthermore, in case of P(3HB-co-8%-3HH) and P(3HB-co-10%-4HB), their single crystals showed a lath-shaped morphology 47) . Each monolamellar part of lath-shaped copolymer single crystals yields a sharp electron diffraction pattern, and this diffraction pattern is consistent with a p 2gg symmetry, which coincides with that of P(3HB) single crystals 11,12,33) . In our study there is no essential difference in the d-spacings of electron diffraction diagrams between P(3HB) copolymer and homopolymer single crystals grown from a mixture of chloroform and ethanol.…”
Section: Poly([r]-3-hydroxybutyrate) Copolymerssupporting
confidence: 66%
See 1 more Smart Citation
“…Furthermore, in case of P(3HB-co-8%-3HH) and P(3HB-co-10%-4HB), their single crystals showed a lath-shaped morphology 47) . Each monolamellar part of lath-shaped copolymer single crystals yields a sharp electron diffraction pattern, and this diffraction pattern is consistent with a p 2gg symmetry, which coincides with that of P(3HB) single crystals 11,12,33) . In our study there is no essential difference in the d-spacings of electron diffraction diagrams between P(3HB) copolymer and homopolymer single crystals grown from a mixture of chloroform and ethanol.…”
Section: Poly([r]-3-hydroxybutyrate) Copolymerssupporting
confidence: 66%
“…15 A. This homogeneous distribution was also observed in case of the other PHB depolymerases from Pseudomonas stutzeri YM1006 11) and Comamonas acidovorans YM1609 12) . Furthermore, the glutathion S-transferase fusion protein with substrate-binding domain of the depolymerase adsorbed on P(3HB) single crystals tightly and homogeneously, suggesting that the substratebinding domain contributes to the adsorption of enzyme on solid P(3HB) without site specificity 101,107,108) .…”
Section: Poly([r]-3-hydroxybutyrate) and Its Copolymerssupporting
confidence: 54%
“…[14,15] SGCs were prepared from an octanol-diluted solution, collected by centrifugation, washed several times with methanol, and then re-suspended in methanol. The samples were prepared by putting drops of crystal suspensions onto cleaned silicon wafers (3 6 3 mm 2 ).…”
Section: Experimental Partmentioning
confidence: 99%
“…Enzymatic degradation of PHB single crystals with PHB depolymerases from Pseudomonas lemoignei (Nobes et al 1996) and R. pickettii T1 (Iwata et al 1997b;Murase et al 2001a) was observed with the transmission electron microscope and the atomic force microscope. These studies demonstrated that enzymatic hydrolysis progresses from the short ends of the lath-like-shaped PHB lamellar single crystals to form cracks along the long axis.…”
Section: Structure and Degradation Of Phb And Copolymersmentioning
confidence: 99%